Scout's progress - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe., 2023)
All of her life, Aelliana Caylon has lived by the rules of her overbearing brother, the head of the Caylon family. Though she is a brilliant mathematician, he has convinced her that she has no worth beyond what value she might have in an arranged marriage. Then, on a dare, she plays a game of chance--and wins a starship. It is her way to escape her home, her planet, her drab life--if she can qualify as a pilot. Enter the accomplished Scout and Master Pilot known only as Daav. Aelliana hires him as her instructor. She finds him gifted teacher. He finds her a quick study. And they also find an unexpected attraction, one that could have dangerous repercussions for them both